2014
DOI: 10.2478/amm-2014-0211
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Toothed Elements in Nanoausferritic Ductile Iron

Abstract: The technology currently used for the fabrication of toothed wheels, gear couplings and chain drums involves the induction hardening process or hardening and tempering after carburising. All these processes take a long time and cause adverse changes in the dimensions and surface quality of products, requiring post-treatment machining to remove the resulting cavities. The paper proposes the implementation of gear elements made of ductile iron with nanoausferritic matrix obtained by a new appropriate heat treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…This is a known mechanism also for ADI materials (see e.g. ). The here quantified austenite transformation confirms such a TRIP effect under quasistatic and crash‐similar loading situations, which might be the reason for the observed high strength values in combination with relatively large elongations at fracture of the ADI qualities under investigation.…”
Section: Results Of Adi 1000 Qualitymentioning
confidence: 82%
See 1 more Smart Citation
“…This is a known mechanism also for ADI materials (see e.g. ). The here quantified austenite transformation confirms such a TRIP effect under quasistatic and crash‐similar loading situations, which might be the reason for the observed high strength values in combination with relatively large elongations at fracture of the ADI qualities under investigation.…”
Section: Results Of Adi 1000 Qualitymentioning
confidence: 82%
“…under mechanical load (TRIP effect). The material properties are very sensitive to the process parameters. Therefore, within the German research project LEA (Light Weight Construction with Cast ADI‐Components ) the process chain was investigated and optimized in detail in order to enable the development of optimized new high strength ADI (Austempered Ductile Iron) in ADI 1000 and ADI 1200 qualities.…”
Section: Introductionmentioning
confidence: 99%
“…Electron diffraction patterns analysis revealed that the microstructure consisted of thin bainitic ferrite plates separated by thin layers of retained austenite. In case of steels this kind of microstructure is called nanobainite [13][14][15], while in ductile iron we can speak of nanoausferrite [6,7]. The average width of ferritic plates was similar for both samples and it was 126 ± 13 nm and 116 ± 7 nm in ADI-1 and ADI-2, respectively.…”
Section: Resultsmentioning
confidence: 70%
“…One of directions of the research work was to produce the alloys with nanocrystalline microstructure and precisely designed phase composition [4][5][6][7]. However, to control the phase composition, especially the content of the retained austenite is not an easy task and needs application of the accurate methods of phases volume fraction determination.…”
Section: Introductionmentioning
confidence: 99%
“…5 shows that the ferrite aggregates build up from many ferrite plates in the same crystallographic orientation. Myszka et al reported that isothermal transformation of ausferrite refines the ferrite plates which tend to form a typical feathery pattern indicating the direction of the plate growth [12]. It is obvious in Fig.…”
Section: Microstructure Evolutionmentioning
confidence: 93%